Enhanced Wound Healing in Superficial Infection Wounds Through α-SMA Upregulation and Collagen Density Increase by Secretome Hypoxia Mesenchymal Stem Cells - Sawitri, Windi; Putra, Agung; Chodijah, Chodijah; Amalina, Nur Dina (Scripta Medica, 2025)
Background/Aim: Superficial wound infections cause delayed remodelling by suppressing the expression of alpha-smooth muscle actin (α-SMA), which inhibits collagen synthesis. Secretomes derived from hypoxic mesenchymal stem cells (SH-MSCs) contain a variety of cytokines and growth factors that contribute to accelerated wound healing and infection suppression. This study aimed to investigate the effects of SH-MSC gel on the expression of the α-SMA gene and the collagen density in the skin tissue of rats with superficial wound infections.Method: The research design utilised a post-test-only control group with a completely randomised format. The study sample consisted of 24 rats with superficial wound infections induced by Staphylococcus aureus bacteria at a concentration of 5 x 107 CFU/mL in 100 µL. The study included four groups: a healthy group, a negative control group, treatment group 1 (T1) receiving a 10 % dose of SH-MSCs gel and treatment group 2 (T2) receiving a 20 % dose of SH-MSCs gel. The expression of the α-SMA gene was analysed through qRT-PCR and collagen density was assessed using Masson's trichrome staining.Results: The qRT-PCR analysis indicated that the α-SMA gene expression was significantly elevated in the T2 group, registering the highest level at 10.03 ± 3.78. This was followed by the T1 group, which had a mean α-SMA gene expression of 4.96 ± 2.77. The negative control treatment group exhibited the lowest level of α-SMA expression, measuring at 0.46 ± 0.09. Additionally, collagen density analysis showed an increase in the T2 group, which had the highest collagen density at 35.68 ± 5.28, followed closely by the T1 group at 34.78 ± 1.72. The negative control group exhibited the lowest collagen density, recorded at 17.39 ± 2.47.Conclusion: The administration of SH-MSCs gel can enhance α-SMA gene expression and increase collagen density in a rat model of superficial wound infection.